AM Versus PM Postoperative Administration of Warfarin With a Mechanical Mitral Valve. (April 2021) - Harris, Justin R.; Hatch, Rachel; Vallabhajosyula, Prashanth; Lo, Yancy; Mowery, Danielle; Patel, Neepa
Background: Currently, there are no guidelines regarding the optimal daily timing of inpatient warfarin administration.Objective: The purpose of this study was to determine whether dosing warfarin in the morning will have a significant impact on therapeutic international normalized ratio (INR) achievement compared with evening administration in mechanical mitral valve patients initiated on warfarin following cardiac surgery.Methods: This was a single-center, pre- and post-retrospective cohort conducted between 2014 and 2018. One-hundred fifty-four adult patients who underwent a mechanical mitral valve replacement or alternative cardiac surgery with a history of a mechanical mitral valve were enrolled. The primary outcome was achievement of therapeutic INR at any time point after initiation of warfarin. Pre-intervention administration timing was 6pm and post-intervention timing was 10am .Results: Baseline characteristics including age, sex, and race were similar between the 2 groups ( P = NS for each characteristic). Therapeutic INR achievement was significantly improved at all time points following 10am warfarin administration compared with 6pm (hazard ratio = 1.69; P = .005). Mean time-to-therapeutic INR was 7.37 days in the post-intervention group and 8.39 days in the pre-intervention group ( P = .073). There were no significant differences in INR >4, bleeding, or thrombotic complications between groups.Conclusion and Relevance: This retrospective analysis suggests that there may be a postoperative benefit in therapeutic INR achievement in mechanical valve patients when dosing warfarin in the morning compared with evening administration. Large-scale studies should be conducted to further elucidate the potential benefit across more heterogeneous populations.